Pengaruh Pemahaman, Penerapan E-System dan Pemberlakuan PTKP Terhadap Kepatuhan Umkm Kabupaten Sleman Dalam Melaporkan SPTDengan Relawan Pajak Sebagai Variabel Moderasi Influence of Understanding, Implementation of E-System and Implementation of Non-Taxab - Efendi, Doni; Azzakhusna, Famita (EBBANK, 2024)
This research aims to find empirical evidence on the influence of understanding taxation, implementing of the tax e-systems and implementing non-taxable income MSMEs on taxpayer compliance with tax volunteers as a moderating variable. The data analysis method used is multiple linear regression and interaction analysis of moderating variables. The results of this research show that understanding taxation and implementing of the tax e-systems has a positive and significant effect on taxpayer compliance. However, the implementation of non-taxable income MSMEs does not have a positive effect on taxpayer compliance and tax volunteers cannot moderate the influence of understanding taxation, implementation of the tax e-system and implementation of non-taxable income MSMEs on taxpayer compliance.